2022
DOI: 10.18280/ijsdp.170431
|View full text |Cite
|
Sign up to set email alerts
|

Study of Public Perception Toward End-of-Life Vehicles (ELV) Management in Indonesia

Abstract: An ELV is a vehicle that has reached the end of its service life or service due to age or because it is unable to be used due to a catastrophic accident and high repair costs. The current methods of destroying ELV vehicles are unregistered, disassembly, destruction, and disassembly. Each procedure must adhere to predetermined guidelines. The purpose of this study is to conduct a survey of dietary knowledge about end-of-life vehicles (ELVs) in Indonesia. As a result, the purpose of this research is to learn abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…In their research, they found that a low level of knowledge largely determines the level of acceptability. Sitinjak et al (2022b) qualitatively attribute public readiness in implementing the rules of emission-free zones in Canada. In their research, they concluded that knowledge is the main component capable of changing the attitude of individuals to comply with rules relating to the environment.…”
Section: The Impact Of Knowledge and Readinessmentioning
confidence: 99%
See 4 more Smart Citations
“…In their research, they found that a low level of knowledge largely determines the level of acceptability. Sitinjak et al (2022b) qualitatively attribute public readiness in implementing the rules of emission-free zones in Canada. In their research, they concluded that knowledge is the main component capable of changing the attitude of individuals to comply with rules relating to the environment.…”
Section: The Impact Of Knowledge and Readinessmentioning
confidence: 99%
“…Although research on the degree of knowledge has been widely applied, there is still very little research in the case of ELV management. Therefore, in their research, (Sitinjak et al, 2022b), advise examining the relationship between knowledge and public acceptability more fully. (Sitinjak et al, 2022b) and Sobri et al, 2021) discovered three major elements in determining people's readiness to accept and implement new regulations, particularly those linked to transportation.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations